2002
DOI: 10.1002/ijc.10566
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of angiogenin, basic fibroblast growth factor and endostatin in patients receiving intensive chemotherapy for acute myelogenous leukemia

Abstract: Angiogenesis seems to be important both in the pathogenesis of acute myelogenous leukemia (AML) and for the susceptibility of AML blasts to chemotherapy. Recent clinical studies even suggest that antiangiogenic therapy can induce disease control in patients with AML relapse. In this context we have investigated the profile of the systemic component of angiogenic regulation in AML by characterizing the serum levels of (i) the angiogenic regulators angiogenin, basic fibroblast growth factor (bFGF) and endostatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
31
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 65 publications
12
31
1
1
Order By: Relevance
“…Under physiological conditions, it is known to circulate at low levels, whereas levels are increased during cancer progression. The reason for this rise in endostatin levels is not clear yet, but increased MMP-activity might play a role [49][50][51][52][53][54][55][56]. Endostatin was described to be able to inhibit proMMP-2 activation and inhibit MMP-2 activity in vitro.…”
Section: Inhibition Of Mmpsmentioning
confidence: 99%
“…Under physiological conditions, it is known to circulate at low levels, whereas levels are increased during cancer progression. The reason for this rise in endostatin levels is not clear yet, but increased MMP-activity might play a role [49][50][51][52][53][54][55][56]. Endostatin was described to be able to inhibit proMMP-2 activation and inhibit MMP-2 activity in vitro.…”
Section: Inhibition Of Mmpsmentioning
confidence: 99%
“…It is unclear whether these elevated endostatin levels are due to direct intratumoral production or a coordinated 'host' response to proangiogenic stimuli, in particular VEGF produced by the cancer (Feldman et al, 2002;Glenjen et al, 2002;Iizasa et al, 2004). What such findings do suggest however is that if this endogenous endostatin is in an active form, further increasing serum endostatin levels to pharmacological levels may not have a significant additional antiangiogenic effect as it is possible that in clinically manifest tumours, once the angiogenic switch has been tripped, raising the levels of endogenous antiangiogenic agents further is not very effective in resetting this.…”
Section: Targeting An Already Overloaded Systemmentioning
confidence: 99%
“…Lai et al [7] did not fi nd signifi cant differences in the median plasma endostatin levels between AML/MDS patients and normal controls. On the other hand Gelenjen et al [11] and Wrobel et al [8] observed increased serum endostatin levels in untreated AML. Furthermore endostatin remains high even after induction chemotherapy.…”
Section: Discussionmentioning
confidence: 95%
“…In chronic lymphocytic leukemia and NHL no difference was found between endostatin plasma levels in complete remission and progressive disease. Morevoer endostatin serum levels did not correlate with disease free survival [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation